Effect of input power on cooling property of a thermoacoustic cooling system with diameter-expanded prime movers. (10th June 2016) - Ueno, So; Sakamoto, Shin-ichi; Orino, Yuichiro; Wada, Takahiro; Inui, Yoshitaka; Watanabe, Yoshiaki
Abstract: We studied a thermoacoustic cooling system driven at low temperatures to make practical use of the system. Aiming to reduce the driving temperature of the thermoacoustic system, we developed a loop-tube-type thermoacoustic system with diameter-expanded two-stage prime movers, i.e., a heat-to-sound transducer. The system drove at 67 °C. Additionally, we developed a prototype for a thermoacoustic cooling system with a diameter-expanded two-stage prime mover. In the experiment, the cooling point temperature was decreased by 4.4 °C from room temperature, i.e., 20 °C. To improve the cooling performance of the prototype thermoacoustic cooling system, we experimentally investigated the effect of increasing the input power on the cooling performance.